2m+3m=65

Simple and best practice solution for 2m+3m=65 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2m+3m=65 equation:


Simplifying
2m + 3m = 65

Combine like terms: 2m + 3m = 5m
5m = 65

Solving
5m = 65

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Divide each side by '5'.
m = 13

Simplifying
m = 13

See similar equations:

| x^3+12x^2=0 | | -13=x-10 | | 100+15p=75+17p | | 4a+5(a+4)= | | x^2+3x^2-4x-12=0 | | 11+3n=n+1 | | 8x-10=66 | | 3g-4(5g-2)+16=-10 | | (5c+12)=(2c-7) | | -6(z+4)+4z= | | 2(3w)+2w=342 | | (x+16)=(3x-8) | | 2(x+1)+25= | | 2*(16)-(7*2+1)/3= | | 4.9*x^2-10*x-21=0 | | 18*(-x-2)-4*(-9+3*x)=-14 | | 5y^2-10y+5=0 | | -9+m+4+6m=6m+1 | | 3q+p-4q-p= | | 2a^2+12a-16=0 | | 5x+6y=148 | | e^20x=0.444 | | 100-x^2y^2=0 | | 2y-7+4y-7= | | 3(4a+b)+6(2a+4b)= | | 3+r=1-r+r | | 2n^9-6n^3+3n^2+6+3n^7+3n^3-6n= | | 121a^2-1=0 | | 4y-7+3y-7= | | 2-33x+2x+9=9 | | y^2+14y+48=0 | | 5x-7y=-16 |

Equations solver categories